Early single sport specialization in a high-achieving US athlete population: Comparing National Collegiate Athletic Association student-athletes and undergraduate students - DiFiori, J. P.; Quitiquit, C.; Gray, A.; Kimlin, E. J.; Baker, R. (Journal of Athletic Training, 2019)
Context Early single-sport specialization and the relative age effect are often cited as improving the chances of sport success. Both concepts suggest that genetics and the environment have little influence on sport success.